Understanding Therapeutic Benefits of Overground Bionic Ambulation: Exploratory Case Series in Persons With Chronic, Complete Spinal Cord Injury - Kressler, Jochen; Thomas, Christine K.; Field-Fote, Edelle C.; Sanchez, Justin; Widerström-Noga, Eva; Cilien, Deena C.; Gant, Katie; Ginnety, Kelly; Gonzalez, Hernan; Martinez, Adriana; Anderson, Kimberley D.; Nash, Mark S. (Archives of physical medicine and rehabilitation, 2014)
To explore responses to overground bionic ambulation (OBA) training from an interdisciplinary perspective including key components of neuromuscular activation, exercise conditioning, mobility capacity, and neuropathic pain. Case series. Academic research center. Persons (N=3; 2 men, 1 woman) aged 26 to 38 years with complete spinal cord injury (SCI) (American Spinal Injury Association Impairment Scale grade A) between the levels of T1 and T10 for ≥1 year. OBA 3d/wk for 6 weeks. To obtain a comprehensive understanding of responses to OBA, an array of measures were obtained while walking in the device, including walking speeds and distances, energy expenditure, exercise conditioning effects, and neuromuscular and cortical activity patterns. Changes in spasticity and pain severity related to OBA use were also assessed. With training, participants were able to achieve walking speeds and distances in the OBA device similar to those observed in persons with motor-incomplete SCI (10-m walk speed, .11–.33m/s; 2-min walk distance, 11–33m). The energy expenditure required for OBA was similar to walking in persons without disability (ie, 25%–41% of peak oxygen consumption). Subjects with lower soleus reflex excitability walked longer during training, but there was no change in the level or amount of muscle activity with training. There was no change in cortical activity patterns. Exercise conditioning effects were small or nonexistent. However, all participants reported an average reduction in pain severity over the study period ranging between −1.3 and 1.7 on a 0-to-6 numeric rating scale. OBA training improved mobility in the OBA device without significant changes in exercise conditioning or in neuromuscular or cortical activity. However, pain severity was reduced and no severe adverse events were encountered during training. OBA therefore opens the possibility to reduce the common consequences of chronic, complete SCI such as reduced functional mobility and neuropathic pain.